SISTEM PEMIDANAAN EDUKATIF TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA - Arpangi Arpangi; Amin Wastoni (Jurnal Pembaharuan Hukum, 2015)
Criminal system that applies to an offense committed by children today are based solely on the nature of pemidanaannya alone. The granting of the criminal system in education is a solution in changing a child’s behavior for the better.The research method used in this study using normative. The results mentioned: 1) The system of sentencing educational for children as a criminal has been regulated in Law Number 3 of 1997, primarily related to the sanctions imposed against the child pursuant to Article 24 paragraph (1), namely to restore to parents, guardians, or foster parents; handed over to the state for education, training and job training; or submit to the Department of Social, Community or social organization engaged in education, training, and job training. Efforts to include children in prisons or detention is a last effort. 2) Barriers to implementation of the criminal system educative for children Indonesian judges in the criminal punishment for children in conflict with the law refers only to the laws that are applied rigidly regardless of background, interests of the child, and the psychological impact on the verdict and without prioritizing justice for children.